VD_FINDINFO HC / 2011 / 67 vom 15. November 2010 - VD Tribunal cantonal (2010)
DIVORCE, OBLIGATION D'ENTRETIEN, ENFANT, MAJORITÉ{ÂGE} | 133 al. 1 CC, 138 al. 1 CC, 145 al. 1 CC, 285 al. 1 CC, 374c CPC, 451 ch. 2 CPC, 452 al. 1ter CPC, 452 al. 2 CPC